The Royal Castle of Kindrochit in Mar (Proceedings of the Society of Antiquaries of Scotland, 1923)
The ruined castle survives mainly as foundations, none of the walls being more than ten feet high. A ground plan based on careful survey has been produced. The chief feature of this castle appears to have been a great mastertower or keep. The style of construction is typical of the fourteenth-and fifteenth-century castles in Aberdeenshire, marked by the very free use of mortar in filling the interstices between the large irregular stones. Small flat pinnings inserted horizontally, which are so characteristic a feature in sixteenth-century work, are here totally absent. The surviving elements and the surrounding topography are considered along with documentary evidence.